2005
DOI: 10.4049/jimmunol.175.6.3882
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Innate Immunity, Inflammation, and Potentiation of DNA Vaccination through Mammalian Expression of the TLR5 Agonist Flagellin

Abstract: Improving DNA vaccination remains a fundamental goal in vaccine research. Theoretically, this could be achieved by molecules encoded by DNA capable of activating TLRs to mimic inflammatory responses generated by infection. Therefore, we constructed an expression vector that allows mammalian cells to express the TLR5 agonist flagellin (FliC) at the cell surface. In vitro, cell lines expressing FliC stimulated production of proinflammatory cytokines and the up-regulation of costimulatory molecules on monocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 61 publications
(55 reference statements)
1
56
0
3
Order By: Relevance
“…The activation of TLR5 by flagellin has an adjuvant-like effect that enhances the immunogenicity of epitopes expressed on the flagellin molecule (13,20). However, Abs generated against the TLR5 activation domains expressed by WT flagellin hamper the host's ability to mount a protective innate immune response against flagellated pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of TLR5 by flagellin has an adjuvant-like effect that enhances the immunogenicity of epitopes expressed on the flagellin molecule (13,20). However, Abs generated against the TLR5 activation domains expressed by WT flagellin hamper the host's ability to mount a protective innate immune response against flagellated pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This PAMP has recently been reported to function as an adjuvant when expressed by a plasmid. 25 Our results suggest that it may also be an interesting adjuvant for a tumor-associated antigen vaccine when expressed from an Ad vector. Further studies are needed to dissect the properties of Ad-PAMPs as vaccination adjuvants.…”
Section: Adenovirus-pamps For Cancer Immunotherapy C Tosch Et Almentioning
confidence: 71%
“…The latter result was unexpected because the P40 has been reported to stimulate TNF-a secretion by human moDCs or monocytes. 18,23,25 Secretion of IL-12 was not induced by transduction with Ad-PAMPs, whereas Ad-CD40L potently upregulated this important Th1-inducing cytokine. It has already been shown that flagellin treatment of human DCs does not stimulate IL-12 secretion.…”
Section: Adenovirus-pamps For Cancer Immunotherapy C Tosch Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…Conjugation of malaria antigens, Pfs25 and AMA1, to nontoxic Pseudomonas aeruginosa ExoProtein S (rEPA) was shown to increase antibody responses by up to 1000-fold. 102 Codelivery of the toll-like receptor (TLR) ligands 103,104 and fusion of antigens to the C3d component of complement 105,106 have shown promise as molecular adjuvants for infectious disease and cancer and may have applications for malaria vaccines.…”
Section: Adjuvant Designmentioning
confidence: 99%